A Surgical Treatment for Adult Muscular Torticollis - Song Ho Chang; Seiji Ohtori; Akihiko Okawa; Koui Kawamura; Hiroshi Saiki; Izumi Nakada; Takashi Shimada; Junichi Nakamura; Kazuhisa Takahashi; Hiroshi Sugiyama (Case Reports in Orthopedics)
Adult presentation of neglected congenital muscular torticollis (CMT) is rare. Therefore, efficacy of surgical treatment for adult CMT is unclear. We experienced a case of neglected CMT in a 28-year-old male patient and report the surgical result here. We conducted unipolar resection at the distal end of the sternocleidomastoid muscle (SCM). After surgery, the range of neck movement and head tilt improved, and his appearance was cosmetically improved despite the long-standing nature of the deformity. We concluded that surgical management of adult patients with neglected congenital muscular torticollis may be a treatment option.